4-Mercaptobenzoic acid as a MALDI matrix for highly sensitive analysis of metals. Issue 5 (10th February 2021) - Sun, Qianqian; Zhang, Shasha; Huang, Weini; Wang, Ran; Chen, Zihan; Cai, Zongwei; Lin, Zian
Abstract : 4-Mercaptobenzoic acid was first introduced as a MALDI matrix for metal analysis. The developed method was successfully applied to the rapid screening and sensitive determination of metals in PM2.5 samples. Abstract : 4-Mercaptobenzoic acid (MBA) is introduced as a matrix for laser desorption/ionization time-of-flight mass spectrometry (MS) analysis of metals, exhibiting matrix-interference-free background, greatly enhanced MS signal intensity, and excellent reproducibility. The developed method was successfully extended for the rapid screening and sensitive determination of ultratrace metals in fine particulate matter (PM2.5 ).